Sports Mega-Events in Asia - Kobayashi, Koji.; Horne, John.; Cho, Younghan; Lee, Jung Woo. (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
"Insightful, thorough and broad ranging, this book takes research on mega-events in exciting new directions. A path breaking work". - Richard Gruneau, Professor Emeritus, Simon Fraser University, Vancouver, Canada "This volume is a well-considered selection of works on the topic of sport mega events in Asia (East and West). It is a must read for all mega event scholars and Asia specialists alike". - Dr., Dr. Barbara Holthus, Deputy Director, German Institute for Japanese Studies, Tokyo, Japan This book is the first comprehensive collection focusing on the hosting of sports mega-events within Asia and their impact on the politics, economics, and culture that shape, and are shaped by, the local idiosyncrasies of host cities and countries across this most culturally diverse continent. From the Olympic Games and single sport World Cups, to the Asian Games and their sub-regional variations, an increasing number of Asian countries have rapidly developed their capacity to host and mobilize large-scale sports events as a cornerstone of their economic growth, national identity formation, and international prestige. This book sets out to fill a gap in the literature and will be of particular relevance to those who are interested in globalization, sports studies, political economy, cultural studies, event management and policy, sociology, media studies, and Asian studies. Koji Kobayashi is Associate Professor in the Center for Glocal Strategy at Otaru University of Commerce, Japan, and Adjunct Senior Lecturer at Lincoln University, New Zealand. John Horne is Visiting Professor in the Graduate School of Sport Sciences, Waseda University, Tokyo, Japan. Younghan Cho is Professor of Korean Studies at the Graduate School of International and Area Studies at Hankuk University of Foreign Studies. Jung Woo Lee is Programme Director of M.Sc. Sport Policy, Management and International Development, Research Director of the Scottish Centre for Olympic Research and Education, and Lecturer in Sport and Leisure Policy at the University of Edinburgh, UK. .
Chapter 1. Introduction - Sports Mega-Events in Asia: Past, Present and Future (John Horne, Koji Kobayashi, Younghan Cho and Jung-Woo Lee) -- Chapter 2. Olympic Games and China's Rise (Susan Brownell) -- Chapter 3. Political Ideologies, Two Chinas Issue, Mega-events in Taiwan (Yu-Wen Chen and Tien-Chin Tan) -- Chapter 4. Politics of the Asian Games and the East Asian Games in China (Marcus P. Chu) -- Chapter 5. Sport Mega-Events and the Contested Terrain of Space, Bodies and Commodities: The Politics and Complexities of Rugby World Cup 2019 (Steven J. Jackson and Koji Kobayashi) -- Chapter 6.Environment Eclipsed: Tokyo 2020 Sustainability Initiatives and the Pandemic Postponement (Robin Kietlinski) -- Chapter 7. Networking Dissent Voices: Korea-Japan Civic Alliance for Olympic Resistance (Kyoung-Yim Kim, Satoko Itani, Kyung Ryeol Lee and Misako Ichimura) -- Chapter 8. Better, Bigger, Bitter - The Rise of the Asian Games in a Toxic Political Environment (Jörg Krieger) -- Chapter 9. Inter-Koreanconnection in 2018 at Sport Mega-Events in Asia: From the Winter Olympic Games in PyeongChang to the Summer Asian Games in Jakarta-Palembang (Jung-Woo Lee and Younghan Cho) -- Chapter 10. The Rugby World Cup 2019 and the Politics of Disaster Recovery in Kamaishi, Japan (Masatoshi Mukoyama and Masayuki Takao).-Chapter 11. FIFA 2022 in Qatar: The Clash of Orientalism and Occidentalism (Kamilla Swart-Arries and Umer Hussain) -- Chapter 12. Sports Events and Infrastructure of Nostalgia: The Indonesian Asian Games 2018 and 'the Spirit of 1962' (Friederike Trotier).
Keywords: Sports -- Sociological aspects; Ethnology -- Asia; Culture; Asia -- Politics and government; Sports sciences; Sport Sociology; Asian Culture; Asian Politics; Sport Science